What impact consumers’ negative eWOM purchase intention? Evidence from Malaysia - Haque, A. K. M. Ahasanul; Kabir, SMH; Tarofder, Arun Kumar; Rahman, Mohammad Moshiur; Almalmi, Abdulqader (Science & Engineering Research Support Society, 2020)
The judgment of consumers conveyed over the internet plays a vital role in the consumer decision making process. Hence, the appearance of electronic word of mouth (eWOM) has become one of the most effective marketing techniques in the 21st century. This research was aiming to determine the predictors of negative eWOM while investigating whether negative eWOM has any specific effect on consumers’ purchase intention. A quantitative research approach was employed while questionnaire data has been collected from more than 250 Malaysian consumers and tested empirically a model that incorporates motives of negative eWOM. Structural equation modelling technique has been used to test the research hypotheses. The findings have shown the different predictors of negative eWOM, which were labelled advice seeking, dissonance reduction and altruism while venting negative feelings proved to be an ineffective motive. The result was able to confirm that negative eWOM has a significant mediating effect on purchase intention. This has contributed insights into the lacking area of consumers’ negative eWOM and argues for identification from marketer’s view, which is an essential step towards consumer’s purchase intention. While in the article, a series of relationships has developed which future researchers may find useful in advancing research in this area.